Experimental Study for Determination of Bed Roughness in Open Rectangular Channel. Issue 1 (May 2020) - Ahmad, N A; Hadzim, M F; Musa, S
Abstract: The experiments are carried out in a straight rectangular compound channel with fixed and nonaggregated bedding. The objectives of this study are to determine the bed roughness and flow characteristic in the open rectangular channel. This study was conducted in the hydrology and hydraulic lab at University Tun Hussein Onn Malaysia. Flume was divided into five parts starting from 1.25m to 6.25m. There are three parameters that tested in a flume with a clear channel, crushed and coarse aggregates. The flow rate was observed with three different values of 0.007m 3 /s, 0.011m 3 /s, and 0.015m 3 /s. The data collected was taken by three parameters that were clearly, crushed and coarse aggregate. From the study, the value derived from the bed acquired in the study was between 0.008 to 0.018 for a clear channel, 0.030-0.013 for the crushed aggregate and 0.016-0.041 which was crushed for coarse aggregate.